Metabolism and Disposition of 2-Hydroxy-4-Methoxybenzophenone, a Sunscreen Ingredient, in Harlan Sprague Dawley Rats and B6C3F1/N Mice; a Species and Route Comparison - Mutlu, Esra (Xenobiotica, 2019)
1. 2-Hydroxy-4-methoxybenzophenone (HMB) is a common ingredient in personal care products and used as an UV stabilizer. In these studies, disposition and metabolism of [(14)C]HMB in rats and mice was assessed following single gavage administration (10, 100, or 500 mg/kg), single IV administration (10 mg/kg), or dermal application (0.1, 1, 10, or 15 mg/kg). 2. Following gavage administration, [(14)C]HMB was well absorbed and excreted mainly in urine (39–57%) and feces (24–42%) with no apparent difference between doses, species or sexes. Distribution of HMB in tissues was minimal in rats (0.36%) and mice (<0.55%). 3. Distribution of HMB following dermal application was comparable to that following gavage administration; no differences between doses, sexes, or species were observed but absorption varied between dose vehicles. Light paraffin oil had the highest absorption and excretion (98% of the HMB dose absorbed). 4. In rats, HMB slowly appeared in the systemic circulation (T(max) ~2–6 h) and had poor bioavailability (F% < 1). 5. Urine metabolites for both species and all routes included HMB, HMB-glucuronide, 2,4-dihydroxybenzophenone (DHB), DHB-glucuronide, and DHB-sulfates, and novel minor dihydroxy metabolites including 2,5-dihydroxy-4-methoxybenzophenone. 6. In vitro hepatic metabolism in mice differed from human and in vivo metabolism especially for phase II conjugates.